IMPLEMENTASI ANALYTICAL HIERARCHY PROCESS (AHP) DALAM PEMILIHAN E-WALLET UNTUK MAHASISWA - Meinarini Catur Utami (Jurnal Ilmiah Matrik, 2019)
Abstract: An electronic wallet is an electronic service to store the data of the payment instrument, such as a payment instrument using the card and/or electronic money, which can also accommodate the funds, to make the payment. The number of similar applications of electronic wallets available in Indonesia leads to confusion of which applications offer many advantages, easy to use and guaranteed transaction security. By using the Analytical Hierarchy Process (AHP) method to conduct research on three popular electronic wallet applications in Indonesia, especially among students, Dana, Go-Pay, and LinkAja. These three electronic wallet applications compare based on pre-defined criteria and sub criteria to be decided by the AHP calculation where Go-Pay is the best E-wallet Application for students to use